“Splicing up” drug discovery. Cell-Based Expression and Screening of Genetically-Encoded Libraries of Backbone Cyclized Polypeptides - Sancheti, Harshkumar (2009)
The present paper reviews the use of protein splicing for the biosynthesis of backbone cyclic polypeptides. This general method allows the in vivo and in vitro biosynthesis of cyclic polypeptides using recombinant DNA expression techniques. Biosynthetic access to backbone cyclic peptides opens the possibility to generate cell-based combinatorial libraries that can be screened inside living cells for their ability to attenuate or inhibit cellular processes thus providing a new way for finding therapeutic agents.